Complications and short-term explantation rate following artificial urinary sphincter implantation: results from a large middle european multi-institutional case series - Kretschmer, Alexander; Hüsch, Tanja; Thomsen, Frauke; Kronlachner, Dominik; Obaje, Alice; Anding, Ralf; Pottek, Tobias; Rose, Achim; Olianas, Roberto; Friedl, Alexander; Hübner, Wilhelm; Homberg, Roland; et al. (Urologia internationalis, 2016)
Background/Aims/Objectives: To analyze perioperative complication and short-term explantation rates after perineal or penoscrotal single-cuff and double-cuff artificial urinary sphincter (AUS) implantation in a large middle European multi-institutional patient cohort. Methods: 467 male patients with stress urinary incontinence underwent implantation of a perineal single-cuff (n = 152), penoscrotal single-cuff (n = 99), or perineal double-cuff (n = 216) AUS between 2010 and 2012. Postoperative complications and 6-month explantation rates were assessed. For statistical analysis, Fisher's exact test and Kruskal-Wallis rank sum test, and a multiple logistic regression model were used (p < 0.05). Results: Compared to perineal single-cuff AUS, penoscrotal single-cuff implantation led to significantly increased short-term explantation rates (8.6% (perineal) vs. 19.2% (penoscrotal), p = 0.019). The postoperative infection rate was significantly higher after double-cuff compared to single-cuff implantation (6.0% (single-cuff) vs. 13.9% (double-cuff), p = 0.019). The short-term explantation rate after primary double-cuff placement was 6.5% (p = 0.543 vs. perineal single-cuff). In multivariate analysis, the penoscrotal approach (p = 0.004), intraoperative complications (p = 0.005), postoperative bleeding (p = 0.011), and perioperative infection (p < 0.001) were independent risk factors for short-term explantation. Conclusions: Providing data from a large contemporary multi-institutional patient cohort from high-volume and low-volume institutions, our results reflect the current standard of care in middle Europe. We indicate that the penoscrotal approach is an independent risk factor for increased short-term explantation rates.